Women Academics’ Intersectional Experiences of Policy Ineffectiveness in the European Context - Täuber, Susanne (Frontiers in Psychology, 2022)
Despite policy efforts targeted at making universities more inclusive and equitable, academia is still rife with harassment and bullying, and opportunities are far from equal for everyone. The present preregistered survey research (N = 91) aimed to explore whether an intersectional approach can be useful to examine the tangible effects of policy ineffectiveness, even when legislative and ideologic constraints limit the possibility to conduct a full-fledged intersectional analysis. Policy ineffectiveness was operationalized as experiences of harassment, discrimination, institutional resistance to gender equality, and retaliation against reporters of misconduct in universities. Policy ineffectiveness was negatively related to women academics’ inclination to pursue an academic career. This relationship was mediated by lower levels of psychological safety associated with policy ineffectiveness. Importantly, women academics who differ from the majority on multiple dimensions show a stronger and more negative relationship between policy ineffectiveness and psychological safety. The study further shows that self-report measures are useful to uncover intersectional privilege afforded to overrepresented groups in academia. The study discusses the benefits of intersectional approaches for designing and implementing effective policies to tackle harassment and inequality in academia, even when the available methodologies are constrained by legislation and ideology. Overall, self-report measurement can have an important function for signalling areas that warrant further intersectional inquiry to ensure that policies serve everyone.